2012
DOI: 10.1007/s00775-012-0875-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of [NiFeSe] and [NiFe] hydrogenases determining their different properties: a computational approach

Abstract: Hydrogenases are metalloenzymes that catalyze the reversible reaction H(2)<->2H(+) + 2e(-), being potentially useful in H(2) production or oxidation. [NiFeSe] hydrogenases are a particularly interesting subgroup of the [NiFe] class that exhibit tolerance to O(2) inhibition and produce more H(2) than standard [NiFe] hydrogenases. However, the molecular determinants responsible for these properties remain unknown. Hydrophobic pathways for H(2) diffusion have been identified in [NiFe] hydrogenases, as have proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 64 publications
0
20
2
Order By: Relevance
“…They have suggested that the concentration of the gaseous substrate in the enzyme affects the enzyme activity. Comparable conclusions have been drawn from the MD simulation results from [NiFeSe] hydrogenase ( 27 ). Baltazar et al ( 27 ) deduce from cavities with trapped H 2 molecules that they either hinder H 2 transport to the active site or promote access by storing gas molecules.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…They have suggested that the concentration of the gaseous substrate in the enzyme affects the enzyme activity. Comparable conclusions have been drawn from the MD simulation results from [NiFeSe] hydrogenase ( 27 ). Baltazar et al ( 27 ) deduce from cavities with trapped H 2 molecules that they either hinder H 2 transport to the active site or promote access by storing gas molecules.…”
Section: Resultsmentioning
confidence: 63%
“…Comparable conclusions have been drawn from the MD simulation results from [NiFeSe] hydrogenase ( 27 ). Baltazar et al ( 27 ) deduce from cavities with trapped H 2 molecules that they either hinder H 2 transport to the active site or promote access by storing gas molecules. Considering the low solubility of H 2 in water, the hydrophobic tunnel system might aid in elevating the H 2 concentration above the surrounding medium level.…”
Section: Resultsmentioning
confidence: 63%
“…It has been well-established that the protein structure surrounding an active site affects the reactivity of an enzyme,[ 14 ] and biomimetic molecules can be employed to learn about the structural and functional properties of the active site. [ 15 ] Our aim is to explore the effect of selenium on the enzyme active site using small molecule model chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, computational methods have been widely used to study gas migration in a number of proteins and MD simulations have successfully allowed the identification of several alternative routes for ligand diffusion (e.g. hydrogenase [26] [28] , myoglobins [29] , [30] , oxidases [31] , [32] and laccases [33] ). Moreover, the combination of MD simulations with Implicit Ligand Sampling (ILS) [29] calculations allows the calculation of the energy cost of transferring any small, apolar molecule (like O 2 or H 2 ) from the solvent to the protein and consequently to compute a 3D free-energy landscape for that specific ligand molecule (e.g [29] , [33] , [34] ).…”
Section: Introductionmentioning
confidence: 99%